Impact of the 2020 New Zealand COVID‐19 lockdown on participants in a community‐based, peer‐led fall prevention program. (4th February 2022) - Smith, Jim; Whittington, Finn; Ackermann, Charlotte; Clarke, Regan; Hoten‐Walker, Georgia; Kubba, Yezen; Low, Chin; Partridge, Karina; Wang, Chris; Dockerty, John D.; Robertson, Linda; Hale, Leigh; et al.
Abstract: Objectives: To explore the impacts of the 2020 New Zealand COVID‐19 lockdown on peer‐led Steady as You Go (SAYGO) fall prevention exercise classes and members, and to develop recommendations for mitigating impacts during future lockdowns. Methods: Semi‐structured phone interviews were conducted with 20 SAYGO program participants and managers following the first COVID‐19 lockdown in New Zealand. Interviews were audio‐recorded, transcribed verbatim and analysed using the General Inductive Approach. Results: Participants were between 67 and 88 years of age, predominantly female (90%) and NZ European (80%), with one participant identifying as NZ Māori. Three themes were constructed from the analysis: Personal Function and Well ‐ Being, Class Functioning and Logistics, and Future Strategies for Classes During Prospective Lockdowns . Participants used a range of strategies to stay connected with each other and continue the SAYGO exercises at home. Most participants and peer‐leaders reported that they maintained physical function during lockdown, although some had feelings of psychological distress and social isolation. Contact systems and resource distribution varied substantially between groups. Classes resumed post‐lockdown with only minor modifications and slightly decreased attendance. Conclusions: Overall, members of this peer‐led model of fall prevention classes demonstrated resilience during the COVID‐19 lockdown, despite some challenges. We propose three recommendations to address the challenges of maintaining existing peer‐led exercise classes in the context of prospective lockdowns: (1) develop a comprehensive contact detail register and plans for each group; (2) delivery of modified exercise classes remotely over lockdown; and (3) implementation of a nationwide IT education and resource program for older adults.